(untitled) (Update Dental College Journal, 2023)
Objective: This systematic review and meta-analysis aimed to establish the most appropriate posterior reference point on the tragus of the ear for orienting the occlusal plane in complete denture prosthesis, addressing the existing confusion regarding this crucial anatomical landmark. Methods: A comprehensive literature search identified 20 relevant articles, with 12 meeting the inclusion criteria as original clinical experimental studies. Statistical analysis was performed to assess the preferred location on the tragus for aligning with the Fox plane. Results: Among the reviewed studies, 72.72% favored the inferior or lower border of the tragus as the optimal posterior reference point for aligning with the Fox plane. This choice was in contrast to the tip or middle point (18.18%) and the superior border (9.09%) of the tragus, which showed less tendency to parallel with the occlusal plane. Conclusion: Based on the findings of this systematic review and meta-analysis, it is concluded that the inferior border of the tragus is the most definitive posterior reference point for establishing the Ala-Tragus line during complete denture prosthesis. This consensus can guide clinicians in achieving accurate occlusal plane orientation and enhance the quality of complete denture prostheses. Update Dent. Coll. j: 2023; 13(2): 38-41